2024
DOI: 10.33988/auvfd.1099535
|View full text |Cite
|
Sign up to set email alerts
|

Geometric analysis of mandible using semilandmark in Hamdani and Awassi sheep

Abstract: The aim of this study is to determine whether or not the breed and sex factors have an effect on the shape in the mandibles of Hamdani and Awassi sheep. A total of 31 mandibles were used. The samples were analyzed via geometric morphometric methods by using semilandmark. In the study, it was determined that the primary principal component accounted for 36.52% of the total shape difference. According to principal component analysis, samples were clustered significantly in terms of breed; whereas, they were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…According to Principal component analysis, the samples clustered significantly in terms of breed. It was stated that there was no clustering in terms of gender [10]. In this study, a significant clustering was observed in terms of three breeds in the results of principal component analysis.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…According to Principal component analysis, the samples clustered significantly in terms of breed. It was stated that there was no clustering in terms of gender [10]. In this study, a significant clustering was observed in terms of three breeds in the results of principal component analysis.…”
Section: Discussionmentioning
confidence: 39%
“…In the study conducted in İvesi sheep and ram, it was seen that PC1 explained % 24.92 of the total variation and PC2 explained %18.525 of the total variation [11]. In the study conducted in Hamdani and İvesi sheep mandible, it was seen that PC1 explained %36,521 of the total variation and PC2 explained %16,614 of the total variation [10]. In this study performed on the mandibles of three different species, it was found that PC1 explained %29.568 of the total variation and PC2 explained %22.169.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the bone shape and size are different. Therefore, many studies have been carried out on the geometric morphometry of various bones (Gündemir et al, 2020;Gürbüz et al, 2020;Demircioğlu et al, 2021;Duro et al, 2021;Gündemir et al, 2021;Demiraslan et al, 2022;Gürbüz et al, 2022;Szara et al, 2022). In this study, it was aimed to reveal the anatomical features and differences of the incus between the donkey and horse belonging to the same family subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The geometric morphometric approach is extensively employed for monitoring alterations in the configuration and dimensions of the skeletal structure, encompassing the skull as an integral system component throughout evolutionary progression. Authors utilize the geometric morphometric method globally to examine variations in shape among diverse populations and scientific disciplines (Demiraslan et al, 2023; Demircioglu et al, 2021, 2022; Gündemir et al, 2020; Jashari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%